Communication—XAFS Analysis of Discharge/Charge Reactions on the Li/CuCl2 Battery Cathode with LiPF6/Methyl Difluoroacetate Electrolyte. Issue 5 (6th February 2016) - Dobashi, Shinsaku; Nakanishi, Koji; Tanida, Hajime; Hashizaki, Katsuo; Uchimoto, Yoshiharu; Hirai, Toshiro; Yamaki, Jun-ichi; Ogumi, Zempachi
Abstract : X-ray absorption fine structure (XAFS) analysis was performed on the CuCl2 cathode in Li/CuCl2 battery with LiPF6 /methyl difluoroacetate (MFA) electrolyte to investigate the valence states of Cu during discharge/charge. X-ray absorption near edge structure (XANES) spectrum indicated that the Li/CuCl2 battery can discharge and charge reversibly. The disproportionation side reaction is confirmed to occur during charging. The side reaction, known to induce battery self-discharge, can be suppressed if reaction Cu + LiCl → CuCl + Li + + e − proceeds completely, which may be accomplished by using a more homogeneous composition in the cathode.